Effects of Co-application of Cadmium-Immobilizing Bacteria and Organic Fertilizers on Houttuynia cordata and Microbial Communities in a Cadmium-Contaminated Field - Yu, Xiumei; Yan, Min; Cui, Yongliang; Liu, Zhongyi; Liu, Han; Zhou, Jie; Liu, Jiahao; Zeng, Lan; Chen, Qiang; Gu, Yunfu; Zou, Likou; Zhao, Ke; et al. (Frontiers in Microbiology, 2022)
Cadmium pollution is a serious threat to the soil environment. The application of bio-based fertilizers in combination with beneficial microbial agents is a sustainable approach to solving Cd pollution in farm soil. The present study investigated the effects of co-application of a Cd-immobilizing bacterial agent and two fermented organic fertilizers (fermentative edible fungi residue; fermentative cow dung) on Houttuynia cordata and its microbial communities in a Cd-polluted field. It showed that both the application of the Cd-immobilizing bacterial agent alone and the combined application of bio-based soil amendments and the bacterial agent effectively reduced > 20% of the uptake of Cd by the plant. Soil nitrogen level was significantly raised after the combined fertilization. The multivariate diversity analysis and co-occurrence network algorithm showed that a significant shift of microbial communities was resulted, in which the microbial populations tended to be homogeneous with reduced microbial richness and increased diversity after the co-application. The treatment of fermentative cow dung with addition of the bacterial agent showed a significant increase in the microbial community dissimilarity (R = 0.996, P = 0.001) compared to that treated with cow dung alone. The co-application of the bacterial agent with both organic fertilizers significantly increased the abundances of Actinobacteria and Bacteroidetes, respectively. The FAPROTAX soil functional analysis revealed that the introduction of the microbial agent could potentially suppress human pathogenic microorganisms in the field fertilized with edible fungi residue. It also showed that the microbial agent can reduce the nitrite oxidation function in the soil when applied alone or with the organic fertilizers. Our study thus highlights the beneficial effects of the Cd-immobilizing bacterial inoculant on H. cordata and provides a better understanding of the microbial changes induced by the combined fertilization using the microbial agent and organic soil amendments in a Cd-contaminated field.